Digestibilidade ileal de frangos de corte alimentados com dietas suplementadas com enzimas exógenas - Barbosa, Nei André Arruda; Bonato, Melina Aparecida [UNESP]; Sakomura, Nilva Kazue [UNESP]; Dourado, Leilane Rocha Barros; Fernandes, João Batista Kochenborger [UNESP]; Kawauchi, Iris Mayumi [UNESP] (My University, 2014)
The experiment was conducted to evaluate the effect of enzyme efficiency in diets with and without nutrient reduction on the ileal digestibility of broilers. A total of 1440 male broiler chicks (Cobb ®) were distributed in a completely randomized design with 4 treatments in a factorial 2 × 2 (two control diets versus supplemented or not with enzyme) with 8 replicates of 45 birds in each experimental unit. The control diets were: positive control (with nutritional levels recommended in the literature for each phase) and a negative control (with reduced energy, calcium and phosphorus). Enzyme supplementation consisted of a combination of enzymes, phytase (100g/t) and complex of amylase, protease and xylanase (500g/t). We evaluated the digestibility of dry matter, crude protein and energy of birds of age 22 and 43 days old. The reduction of nutrients in the diets caused a reduction in the negative control digestible energy and protein digestibility, however, the addition of enzyme mix in the negative control increased the digestible energy in two phases, and the digestibility of protein at 22 days old. The addition of enzymes improved the digestibility of nutrients in diets with nutrient reduction.
Ileal digestibility of broilers fed diets supplemented with exogenous enzymes
Keywords: Amylase; Broilers; Nutrition; Phytase; Protease; Xylanase